Angles and geometric shapes, but not lines, in melanocytic lesions may be helpful in the clinical diagnosis of melanoma. (4th August 2014) - Betti, R.; Cerri, A.; Vergani, R.; Agape, E.; Menni, S.
Abstract Background Geometric shapes have been suggested to be found in malignant melanomas. We have observed a number of melanomas presenting with linear and incomplete angulated figures. Objective To verify the assumption that geometric shapes, a linear border and/or incomplete angulated figures may indicate a potential melanoma. Methods Patients with surgically removed melanocytic lesions were admitted to the study. We evaluated the presence of a sharp linear demarcation, the presence of contiguous lines resulting in the formation of angle/s and the presence of complete geometric figure. We distinguished the obtained results into melanoma and benign melanocytic naevi. Results A total of 471 melanomas and 1979 melanocytic naevi were collected. Linear borders, angles and geometric figures were observed in 42 melanomas and in 75 benign melanocytic naevi. Angles with incomplete geometric configuration were observed in 21 melanomas and in 37 benign naevi (21/471 vs. 37/1979, 4.24% vs. 1.87%; P < 0.0016); complete even if irregular geometrical figures in 12 melanomas and 17 naevi (12/471 vs. 17/1979, 2.54% vs. 0.85%; P < 0.005). The presence of line(s) did not significantly differed in the two considered groups. Conclusions Melanocytic lesions with angulated shapes and complete geometrical configurations might indicate a suspect melanoma. Only sharp linear demarcation of the lesion do not seem to be significantly associated with melanoma suspicion.